Decreased influenza activity during the COVID-19 pandemic in Ghana, 2020 - Asante, Ivy Asantewaa; Nyarko, Stephen Ofori; Awuku-Larbi, Yaw; Obeng, Richard Asomadu; Sarpong, Gifty Mawuli; Amenuvor, Esinam Aku Apefa; Adusei-Poku, Mildred; Boatemaa, Linda; Magnusen, Vanessa; Wutsika, Jennifer; Ago, Samuel; Kwasah, Lorreta; et al. (Frontiers in Public Health, 2024)
The COVID-19 pandemic had a significant effect on influenza activity globally. In this study, we analyzed trends of influenza activity in 2020 during the COVID-19 pandemic in Ghana. This was a crosssectional study using active prospective influenza surveillance data from 29 sentinel sites. At the sentinel sites, we enrolled patients presenting with symptoms based on the WHO case definition for influenzalike illness (ILI) and severe acute respiratory illness (SARI). Oro and nasopharyngeal swabs were collected from patients and tested for the presence of influenza viruses using specific primers and probes described by the US-CDC. The percentage of positivity for influenza between 2017-2019 and 2021 was compared to 2020. Using the test for proportions in STATA 17.0 we estimated the difference in influenza activities between the two periods.